TDM1 Regulation Determines the Number of Meiotic Divisions - Cifuentes, Marta; Jolivet, Sylvie; Cromer, Laurence; Harashima, Hirofumi; Bulankova, Petra; Renne, Charlotte; Crismani, Wayne; Nomura, Yuko; Nakagami, Hirofumi; Sugimoto, Keiko; Schnittger, Arp; Riha, Karel; et al. (PLoS genetics, 2016)
Cell cycle control must be modified at meiosis to allow two divisions to follow a single round of DNA replication, resulting in ploidy reduction. The mechanisms that ensure meiosis termination at the end of the second and not at the end of first division are poorly understood. We show here that Arabidopsis thaliana TDM1, which has been previously shown to be essential for meiotic termination, interacts directly with the Anaphase-Promoting Complex. Further, mutations in TDM1 in a conserved putative Cyclin-Dependant Kinase (CDK) phosphorylation site (T16-P17) dominantly provoked premature meiosis termination after the first division, and the production of diploid spores and gametes. The CDKA;1-CYCA1.2/TAM complex, which is required to prevent premature meiotic exit, phosphorylated TDM1 at T16 in vitro. Finally, while CYCA1;2/TAM was previously shown to be expressed only at meiosis I, TDM1 is present throughout meiosis. These data, together with epistasis analysis, lead us to propose that TDM1 is an APC/C component whose function is to ensure meiosis termination at the end of meiosis II, and whose activity is inhibited at meiosis I by CDKA;1-TAM-mediated phosphorylation to prevent premature meiotic exit. This provides a molecular mechanism for the differential decision of performing an additional round of division, or not, at the end of meiosis I and II, respectively.
Keywords: Anaphase-Promoting Complex-Cyclosome; Phosphorylation; genetická epistáze; proteiny huseníčku; Genes, Dominant; Chromosomes, Plant; fosforylace; podjednotky proteinů; Protein Binding; Models, Biological; mutace; Phosphothreonine; Tubulin; Arabidopsis Proteins; Meiosis; cykliny; Tetraploidy; fosfothreonin; Arabidopsis; meióza; tetraploidie; Protein Subunits; vazba proteinů; tubulin; biologické modely; anafázi podporující komplex; Epistasis, Genetic; genetické testování; Cyclins; Genetic Testing; chromozomy rostlin; Mutation; dominantní geny